Virtual Geo-Hazard Monitoring andAsset Management System (ViGMAS) - R.C. Omar; H. Taha; R. Roslan; I.N.Z. Baharuddin; M.M Fared; W.S.W Hashim (Lowland Technology International, 2020)
This paper describes a virtual geo-hazard monitoring and assetmanagement system (ViGMAS) which implements a near realtimesatellite image processing system to extract relevantenvironmental and meteorological parameters. The systemfocuses on geo-hazard monitoring by accumulating informationabout the earth using remote sensing technologies which can beapplied in disaster risk management. This system also includesasset management program for managing assets by inventoryand assessment through integration with Geographic InformationSystem (GIS). Mapping and inventory by GIS help to improveefficiencies and assist in decision making based on gathereddata. The system was designed to manage preliminaryconstruction and management planning, health performance, riskand costs of management asset through 4D visualization whichintegrates existing data and primary data obtained from a dataset of mapping terrain and satellite that will fit in the system ofvirtual reality